A fine motor skill training system using multi-fingered haptic interface robot. Issue 84 (December 2015) - Endo, T.; Kawasaki, H.
Abstract: This paper focuses on a haptic training system for fine motor skills using multiple fingers. To transfer skills involving such fine motor tasks, instruction on how to move the fingers and use fingertip forces is essential. In this paper, we propose an optimal method for transmitting knowledge regarding fingertip forces from trainer to trainee; we then construct a haptic training system based on the proposed method. The resulting system conveys knowledge of fingertip forces and positions in three-dimensional space by combining an image display system with a five-fingered haptic interface robot capable of alternating force presentation. Finally, we describe several experiments carried out to optimize and evaluate the performance of the proposed method. Abstract : Highlights: We proposed optimal switching method for transferring multiple fingertip forces. Based on the proposed method, a haptic training system was developed. The proposed method enhanced the training effect compared with our earlier method.